O abrigo rupestre da foz do Tua no contexto da Arte Paleolítica e Pós-Paleolítica do noroeste da Península Ibérica - Teixeira, Joana Castro; Sanches, Maria de Jesus (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2017)
The Foz do Tua Rockshelter is located in river Douro hidrographic basin. The rockshelter use, during prehistory, occurs according to a long-term chronology, which goes from 30 000/20 000 BP to 4 000 BP. There are also Contemporary engravings. Within Foz do Tua Rockshelter we can count at about half a hundred of engraved and painted panels according to various techniques and compositions. The present paper exposes the investigation that has been made in Foz do Tua, describes its iconography and discusses the chronology of its panels/ motifs, based on the regional archaeological data available for Prehistory and Rock art of the northwest Iberia.